Rancang Bangun Aplikasi Pengarsipan Berkas Berbasis Android pada Kantor Notaris NJ - Dian Novita Sari; Muhammad Imron Rosadi (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2023)
Archives is a collection of records or documents containing information on the activities and transactions of an organization, institution, and company. The Notary office NJ notary has been using conventional methods for archiving files, which requires a considerable amount of time when needing to retrieve such data in the future. Due to this conventional approach, human errors often occur. The purpose of this research is to develop an Android-based file archiving application for the Notary Office of NJ. The waterfall method is utilized for system development. The application is designed using Figma and built using android studio. Based on the results of black box testing, the developed application can be used without any errors or bugs. Additionally, Usability testing was conducted to measure the level of usefulness, with a learning aspect score of 96%, an efficiency aspect score of 0,024 goals/sec, an average overall relative efficiency of 82.1%, and an error aspect score of 0.04. Based on these results, it can be concluded that the application is suitable according to the usability testing, and it is suitable for implementation in the notary office of NJ